TAMPAH BAMBU TRADISIONAL SEBAGAI MEDIA MENGGAMBAR UNTUK PENGEMBANGAN KREATIVITAS ANAK - Ismanto, Adi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Tampah is a traditional handicraft product made from woven bamboo. Along with the development of technology and modernization, traditional tampah began to be abandoned replaced with other materials such as plastic and metal. To anticipate this, there is an innovation of tampah products that function as decorative elements or decorations by adding paintings on the back or inside of the appearance. The results of the paintings on the bamboo show increase the value of objects and become a means of creativity development activities for various groups, especially for children. Mitra Yayasan Rumah Pagi Bahagia has a mission to create education and independence for foster children. The training method was carried out to develop children's creativity through drawing activities on traditional bamboo tampah which was carried out into 2 stages, which began with questionnaires and exposure to knowledge about traditional bamboo tampah and drawing mix media. Then, stage 2 of the activity will be continued by looking for references and image ideas which are then implemented on bamboo patches, so as to display unique and creative decorative products. It is expected that from this activity, Rumah Pagi Foundation foster children will receive education about drawing mix media and multiply creative activities for the development of creativity that allows them to produce decorative products from bamboo patches. Through this training activity, can be concluded that most of the children know traditional bamboo tampah (80%), but all of them do not know that bamboo tampah can be used as a drawing medium (100%) and all foster children feel and get new experiences in drawing activities using traditional bamboo tampah. The activity of drawing mix media on traditional bamboo patches that has been carried out to children of Rumah Pagi Bahagia Foundation, is expected to provide encouragement for the development of creativity through the process of finding reference ideas and their implementation to produce works with different media.